LEGAL REVIEW OF THE TAKEOVER OF CONSUMER SHOPPING POINTS BY MINIMARKET EMPLOYEES FROM THE PERSPECTIVE OF CRIMINAL ACTS OF FRAUD - Anggi Anggraini Putri; Kristian; Claudia Yuni Pramita (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Advances in human intelligence have shaped new patterns of behavior, one of which is the habit of making transactions. Transactions take place everywhere, including minimarkets. As a result, competition and large-scale marketing promotions have emerged as solutions to retain customers. Shopping points have become a solution that has unique economic appeal for consumers. This phenomenon has opened up new motives for criminal acts. This study examines the phenomenon of minimarket employees taking over consumer shopping points as a form of fraudulent act that can be criminalized. The focus of the study is on the position of shopping points as economic assets that have exchange value and the construction of criminal liability for the perpetrators. The results of the study show that shopping points are intangible digital assets that have economic value, so legally they are the property of consumers that must be protected. Juridically, the actions of these employees fulfill the elements of criminal fraud as regulated in Article 495 of Law Number 1 of 2023 concerning the Criminal Code. Law enforcement against this practice recommends strict measures by minimarkets as a form of consumer protection within the company, and recommends the imposition of criminal sanctions if this action occurs repeatedly under the provisions of the New Criminal Code in order to provide a deterrent effect and ensure legal certainty in the retail sector.